Climate adaptation of biodiversity conservation in managed forest landscapes - Kristoffer Hylander; Caroline Greiser; Ditte M. Christiansen; Irena A. Koelemeijer (Conservation Biology, 2022)
Conservation of biodiversity in managed forest landscapes needs to be complemented with new approaches given the threat from rapid climate change. Most frameworks for adaptation of biodiversity conservation to climate change include two major strategies. The first is the resistance strategy, which focuses on actions to increase the capacity of species and communities to resist change. The second is the transformation strategy and includes actions that ease the transformation of communities to a set of species that are well adapted to the novel environmental conditions. We suggest a number of concrete actions policy makers and managers can take. Under the resistance strategy, five tools are introduced, including: identifying and protecting forest climate refugia with cold‐favored species; reducing the effects of drought by protecting the hydrological network; and actively removing competitors when they threaten cold‐favored species. Under the transformation strategy, we suggest three tools, including: enhancing conditions for forest species favored by the new climate, but currently disfavored by forest management, by planting them at suitable sites outside their main range; and increasing connectivity across the landscape to enhance the expansion of warm‐favored species to sites that have become suitable. Finally, we suggest applying a landscape perspective and simultaneously managing for both retreating and expanding species. The two different strategies (resistance and transformation) should be seen as complementary ways to maintain a rich biodiversity in future forest ecosystems.